CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER, RETURN ON ASSET, PRICE TO BOOK VALUE SEBAGAI FAKTOR PENENTU RETURN SAHAM - Asmi, Tri Laksita (Management Analysis Journal, 2014)
The Â purpose Â ofthis Â studyistoexamineandanalyze Â thefinancial Â ratio Â is Â measuredwithCurrent Â Ratio, Â Debt Â toÂ Equity Â Ratio, Â Total Â Asset Â Turnover, Â Return Â On Â Asset, Â Price Â to Â Book Â Value Â towards Â share Â return. Â TheÂ populationin Â this Â study Â areallReal Â Estate Â and Â Property Â Industri Â Listed Â inthe Â indonesia Â stock Â exchange sinceÂ period 2012-2013, with the total of47companys. Thestudysamplewas takenby purposive sampling method, withÂ the Â total Â of Â 31company. Â This Â study Â usesdata Â analysisof Â multiple Â linear Â regression Â analysis Â to Â estimated Â ofÂ dependent variableâs value from independent variableâs. Based onthe research results, it can be known that onlyÂ price to book value has a significant effect toward share return and for current ratio, debt to equity ratio, totalÂ asset turnover, return on asset has not a significant effect toward share return.